Analysis of agricultural based commodities in Bolaang Mongondow Regency, North Sulawesi, Indonesia. Issue 1 (March 2021) - Diansari, P; Yunus, S R; Arsyad, M; Lanuhu, N; Jamil, M H; Mahyuddin,
Abstract: The agricultural sector is still an important, and potential sector when compared with the other sectors. Therefore, the development of agricultural sector should prioritize the potential of environmental resources and the ability of its people. This study aims to identify agricultural based commodities in Bolaang Mongondow Regency, North Sulawesi Province. This study used secondary data from Agriculture and Plantation Agency, Bolaang Mongondow Regency and North Sulawesi Province in 2012-2016 and then analyzed using the Location Quotient method. The results show there are 15 agricultural based commodities in the regency which are potential to develop. They are green beans, soybeans, corn, rice, candlenut, coffee, cocoa, pineapple, mango, mangosteen, spinach, long beans, kale, eggplant, and potatoes. As for now, the commodities that are the government's main focus are soybeans, corn, rice, cocoa, pineapple, and potatoes.